Evaluasi Pendidikan dan Pelatihan di Badan Pengembangan SDM Pemerintahan Provinsi Sumatera Utara - Alfa, Lutfiah Malaya; Alyani, Filza; Puspita, Dhea (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the implementation of the evaluation of education and training programs organized by the Human Resources Development Agency of North Sumatra Province. The main focus of this study is to assess the effectiveness of training using the four-level evaluation approach developed by Kirkpatrick, namely evaluation at the level of reaction, learning, behavioral change, and final results. The methodological approach used is descriptive qualitative, with data collection techniques through direct observation and in-depth interviews with training participants and program organizers. The study shows that the training program makes a significant contribution to improving participant competence, especially in terms of technical skills and professional attitudes. In addition, there was also a positive shift in the work behavior of participants after participating in the training. However, the implementation process still faces several obstacles, such as limited facilities and less than optimal training time. This evaluation has a strategic role in ensuring the quality of the training program and becoming the basis for decision making for continuous improvement. Therefore, the results of this evaluation are not only useful in the context of the program being studied, but can also be a reference in designing training policies based on needs for human resource development in the public sector in general.